Government Size and Intersectoral Income Fluctuation : An International Panel Analysis - Kim, Daehaeng; Lee, Chul-In. (Washington, D.C. : International Monetary Fund, 2007)
Using the between-sector variation in income as a new measure of economic uncertainty, this paper proposes simple models and supportive empirical evidence for the causal relations between economic uncertainty and government size in the open economy setting. Key empirical findings include: (1) a larger government reduces economic uncertainty, and, at the same time, (2) an economy facing higher uncertainty has a larger government. However, (3) the government tends to resort to redistributive policies to reduce the uncertainty, while (4) government direct spending is also an effective option for the purpose. The study also finds that (5) cross-sectional measure of economic uncertainty tends to rise when a country becomes more open to international trade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet